2021
DOI: 10.1097/md.0000000000024210
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Gegen Qinlian Decoction on clinical prognosis and islet function for type 2 diabetic mellitus

Abstract: Background: With the development of social economy, people's lives are improving day by day. Chronic diseases represented by diabetes have gradually entered people's field of vision. At present, about 415 million people in the world suffer from diabetes, of which more than 90% are Type 2 diabetic mellitus (T2DM), which causes severe physical and mental pain to patients and their families, and also imposes a huge burden on the health care system. Animal experiments and clinical studies both show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Hypoglycemia, nausea, vomiting and diarrhea are the most common adverse reactions of metformin. 18 The results of the study showed less adverse reactions in the observation group than the control group, suggesting GQD plus metformin has better safety. GQD is traditionally used for diarrhea and dysentery in TCM.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Hypoglycemia, nausea, vomiting and diarrhea are the most common adverse reactions of metformin. 18 The results of the study showed less adverse reactions in the observation group than the control group, suggesting GQD plus metformin has better safety. GQD is traditionally used for diarrhea and dysentery in TCM.…”
Section: Discussionmentioning
confidence: 81%
“…Clinical effect assessment is described below. 18 Statistical Analysis: Data were analyzed using SPSS 22.0 (IBM, USA). Continuous, normally distributed variables were presented as mean ± SD, and Student's t-test was used to compare the differences between the two groups.…”
Section: Methodsmentioning
confidence: 99%
“…Although GQD and metformin did not suppress the FBG level after islet β-cells were extremely decreased, they are still promising medicines in treating diabetes. Firstly, GQD and metformin could be used as effective medications to treat patients in the early stage of T2D or pre-diabetes [ 55 , 56 ]. Furthermore, the proliferation of α-cells stimulated by GQD and metformin provided an important source for α-cell to β-cell reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…GQD has been used to treat XIAOKE (T2DM) in TCM clinics. Previous clinical research has shown that it had a good effect of GQD decreasing blood glucose, improving islet function, reducing the insulin resistance index, and insulin secretion index in patients with T2DM (Ren et al., 2021; Ryuk et al., 2017). Meanwhile, GQD is often used to treat T2DM combined with hypoglycemic drugs (saxagliptin, Sax, metformin) in clinics.…”
Section: Introductionmentioning
confidence: 99%